Pelepasan Doxorubicin (DOX) Dari Hidroksiapatit (HA) Dengan Variasi Nilai pH Dan Rasio Dox-Ha / Phosphat Buffer Saline (PBS) - Nursyaniati Nursyaniati; Ahmad Fadli; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite was a material that could be used as drug delivery in cancer by doxorubicin adsorbed on to hydroxyapatities surface. The purpose of this research were to study the effect of variation of pH and ratio DOX-HA : PBS on speed release. HA was suspended in 10 ml of DOX (100 ppm) strirred using a magnetic stirrer with speed 250 rpm at temperature 37ºC for 24 hours. After that it filtered at vacuum pressure for 24 hours. The release of DOX from 270 mg HA powder were soaked in 350 ml of solution PBS (pH 5,6 dan 7,4). The samples were taken every two hours until 120 hours. The concentration of DOX’s released were analyzed by UV-Vis. Furthermore, the DOX-HA powder were characterized with FTIR. There was HA and DOX function group which meant, there were any DOX’s adsorbed and released from HA used powder. If higher pH and more HA powder were used, would effect the released of DOX were more effective. The released in the first 40 hours of DOX concentration released in PBS was maintained at 1,25 and 6,92 ppm for each pH 7,4 and 5,6. While for mass HA variations maintained at 0,625; 3,541; 4,508; and 4,958 ppm for each 0,2; 0,3; 0,4 dan 0,5 gram.Keywords : doxorubicin, drug delivery, hydroxyapatite, phosphat buffered saline, release.